Application of MXene (at) PANI (at) Au composite material in detection of sepsis biomarkers

The biosensor fabricated using MXene@PANI@Au composite material solves the problems of complex operation and single biomarker detection in existing technologies, enabling simplified and low-cost simultaneous detection of PCT and IL-6, which has revolutionary rapid diagnostic significance.

CN121293492APending Publication Date: 2026-01-09SHANGHAI CHEST HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511337169.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing PCT and IL-6 detection technologies are complex to operate, costly, require professional personnel to operate, and most sensors can only detect a single biomarker, making early diagnosis of sepsis difficult.

Method used

Using MXene@PANI@Au composite material, PANI was synthesized in situ via wet chemical method and one-pot method to form MXene@PANI@Au tertiary composite material, which was used to prepare a bioimmunosensor to achieve simultaneous detection of two biomarkers.

Benefits of technology

It simplifies the detection process, reduces costs, and enables the simultaneous detection of PCT and IL-6 in the same sample at the same time, shortening the total detection time and improving the sensitivity and specificity of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293492A_ABST
    Figure CN121293492A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical immunosensors, and provides an MXene (at) PANI (at) Au composite material and application thereof in detection of sepsis biomarkers. Through research and development of the MXene-coated PANI-coated Au composite material, the problems of high operation complexity, high cost, potential cross reaction, need of professional operation and need of detection in a specific place in the current detection process are solved. According to the MXene-coated PANI-coated Au biological immunosensor disclosed by the invention, the two electrodes can share the same sample, the same time and the same detection environment. The results of the two markers can be obtained at the same time through one-time sample adding. The method not only realizes fast, but also shortens the total detection time fundamentally, which has revolutionary significance for clinical scenes needing fast diagnosis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical immunosensor technology, specifically to a composite material based on MXene@PANI@Au, its preparation method, and its application in detecting biomarkers such as PCT and IL-6 proteins. Background Technology

[0002] Sepsis is a life-threatening infection caused by pathogens entering the bloodstream, resulting in more than 11 million deaths annually. Its early, nonspecific symptoms pose a significant challenge to diagnosis, leading to delays in treatment. Therefore, early diagnosis is crucial for reducing this high mortality rate. Under normal circumstances, the concentration of interleukin-6 (IL-6) in human serum is relatively low, typically not exceeding 75 picograms per milliliter. When IL-6 levels exceed this threshold, the inflammatory state can progress to severe disease, making IL-6 a key biomarker for monitoring health and disease progression. Procalcitonin (PCT) is also a key biomarker for assessing sepsis severity, with normal serum levels below 0.1 nanograms per milliliter, rising sharply during bacterial infections. Although existing methods can detect PCT or IL-6, achieving highly sensitive and specific protein analysis remains challenging.

[0003] Therefore, developing simple, rapid, and sensitive protein detection technologies is crucial for early sepsis surveillance. In recent years, significant progress has been made in the detection of PCT and IL-6, resulting in a variety of analytical methods, including colorimetric analysis, flow cytometry, polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA), and chemiluminescent immunoassay (CLIA).

[0004] However, these technologies face challenges such as operational complexity, high cost, potential cross-reactivity, the need for specialized personnel, and the requirement for hospital-based testing. Furthermore, most current sensors target only a single protein. Relying solely on a single biomarker to diagnose sepsis can lead to misdiagnosis. Summary of the Invention

[0005] This invention aims to overcome the aforementioned shortcomings and provide a bioimmunosensor based on MXene@PANI@Au, its preparation and synthesis method, and its application in detecting biomarkers. The MXene@PANI@Au bioimmunosensor of this invention enables two electrodes to share the same sample, at the same time, and in the same detection environment. With a single sample addition, results for two biomarkers can be obtained simultaneously. This not only achieves speed but also fundamentally shortens the total detection time, which is revolutionary for clinical scenarios requiring rapid diagnosis.

[0006] The present invention discloses a composite material MXene@PANI@Au, characterized in that: the MXene@PANI@Au composite material is composed of MXene, PANI and Au.

[0007] The method for preparing the composite material MXene@PANI@Au provided by this invention is further characterized in that:

[0008] PANI was synthesized in situ in a mixed solution of MXene and Au NRs via wet chemical method and one-pot method, forming a tertiary composite material of MXene@PANI@Au.

[0009] The method for preparing the composite material MXene@PANI@Au provided by this invention is further characterized in that:

[0010] In the process of in-situ synthesis of PANI, aniline is used as the monomer, and an oxidant and an initiator are also required.

[0011] The method for preparing the composite material MXene@PANI@Au provided by this invention is further characterized in that:

[0012] The preparation method of the MXene is as follows:

[0013] SX1. Mix lithium fluoride with hydrochloric acid and stir at room temperature. The mass ratio of lithium fluoride to hydrochloric acid is 1:3-10.

[0014] SX2. Add the MAX phase and heat at 30-50℃ for 40-60 min. The mass ratio of the MAX phase to lithium fluoride is 1:0.8-3.

[0015] SX3. Wash with water and centrifuge until pH reaches 6.5-7.5;

[0016] SX4. Add ethanol and sonicate to obtain a black precipitate, which is MXene.

[0017] The method for preparing the composite material MXene@PANI@Au provided by this invention is further characterized in that:

[0018] The preparation method of the Au NRs is as follows:

[0019] SA1. Mix tetrachloroauric acid and hexadecyltrimethylammonium bromide, with the tetrachloroauric acid solution concentration being 0.01-0.04M;

[0020] SA2. Add ice-cold sodium borohydride solution, mix quickly, and let stand at room temperature for 2-3 hours to obtain the seed solution. The concentration of sodium borohydride solution is 0.01-0.03M, and the volume ratio of tetrachloroauric acid solution to sodium borohydride solution is 1:1-5.

[0021] SA3. Prepare the growth solution, namely, a mixed solution containing tetrachloroauric acid, hexadecyltrimethylammonium bromide, silver nitrate, hydrochloric acid, and ascorbic acid;

[0022] SA4. Add the seed solution prepared in S2 to S3, mix well, and let stand at room temperature for 7-9 hours.

[0023] The method for preparing the composite material MXene@PANI@Au provided by this invention is further characterized in that:

[0024] S1. Prepare a mixed solution of hydrochloric acid and aniline, and a mixed solution of ammonium persulfate and hydrochloric acid;

[0025] S2. Centrifuge the Au NRs;

[0026] S3. Mix MXene, Au NRs and water to form a homogeneous solution;

[0027] S4. Add the mixed solution of hydrochloric acid and aniline from S1 and continue stirring for 2-5 hours;

[0028] S5. Add the mixed solution of ammonium persulfate and hydrochloric acid from S1 and continue stirring for 2-5 hours.

[0029] Furthermore, this invention also suggests the application of the composite material MXene@PANI@Au in the preparation of biosensors.

[0030] The preparation method of the above-mentioned biological immune sensor is as follows:

[0031] After drying MXene@PANI@Au on a screen-printed electrode, add the EDC and NHS activated antibody onto the electrode and incubate for 15-30 minutes.

[0032] The mass ratio of EDC to NHS is 1:1-2; the activation time is 15-20 min; and 5-7 μL of PCT antibody or IL-6 is added to each electrode.

[0033] Furthermore, this invention also suggests the application of the composite material MXene@PANI@Au in the preparation of products for detecting / identifying PCT and / or IL-6 proteins.

[0034] Furthermore, this invention also suggests the application of the composite material MXene@PANI@Au in the preparation of products for sepsis diagnosis or early screening.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] (1) The method of the present invention is simple to prepare, the reaction conditions are relatively mild, and the composite material is synthesized in a one-pot method;

[0037] (2) The MXene@PANI@Au synthesized in this invention has a high yield of 80-85%, and the synthesized product is relatively stable;

[0038] (3) The morphology of MXene@PANI@Au obtained by the present invention can be controlled by adjusting the ammonium persulfate content and stirring time. It can be controlled by adjusting the amount of initiator and the polymerization time, from complete coating of PANI to partial exposure of Au NRs, and finally to a thin layer on the surface of MXene and Au. When the added ammonium persulfate content is 5mg, the stirring time is 4 hours.

[0039] (4) The MXene@PANI@Au immunosensor obtained in this invention has the function of detecting two different proteins and has good stability. Figure 9 After 31 days, the current remained at 82%, proving that it has good performance over a long period of time. Attached Figure Description

[0040] Figure 1 This is a scanning electron microscope (SEM) image of Example 1.

[0041] Figure 2 For Figure 1 Select a high-resolution electron microscope (HTEM) image.

[0042] Figure 3 XRD patterns of MXene, PANI, Au NRs, and MXene@PANI@Au NRs.

[0043] Figure 4 Raman plots for MXene, PANI, and MXene@PANI@Au NRs.

[0044] Figure 5 The DPV response of PCT standard protein at different concentrations.

[0045] Figure 6 Linear fitting for different concentrations of PCT.

[0046] Figure 7 DPV response of IL-6 standard protein at different concentrations.

[0047] Figure 8 DPV response of IL-6 standard protein at different concentrations.

[0048] Figure 9 Long-term stability response of PCT (left) and IL-6 (right) sensors.

[0049] Figure 10 Selective response of PCT (top) and IL-6 (bottom) sensors.

[0050] Figure 11 The responses of real human serum from different groups. Detailed Implementation

[0051] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.

[0052] Example 1. Preparation of MXene@PANI@Au composite material

[0053] This embodiment provides a method for preparing MXene@PANI@Au composite materials, including the following steps:

[0054] S1. Prepare a mixed solution of lithium fluoride and hydrochloric acid. Stir the mixed solution at room temperature, then add the MAX phase and heat while stirring. Finally, wash with water and centrifuge until the pH reaches 6.5-7.5. Add ethanol and sonicate to obtain a black precipitate, MXene.

[0055] In this mixture, the mass ratio of lithium fluoride to hydrochloric acid is 1:3-10. Preferably, 3g of lithium fluoride is combined with 25-40mL of 12M hydrochloric acid to form a black mixed solution. More preferably, 3g of lithium fluoride is combined with 30mL of 12M hydrochloric acid. In the research of this invention, it was found that the LiF / HCl ratio is not a process parameter that can be changed at will, but a key inventive point that directly determines the core structure and performance of the final product. Through a large number of experiments, we discovered and confirmed this strict structure-property relationship: that is, only when the above-mentioned appropriate ratio is used can the nanostructure of MXene be customized in a 'programmable' manner, thereby actively and predictably optimizing its subsequent biological functional performance (such as antibody loading).

[0056] The mass ratio of MAX phase (Jilin Yiyi Technology, 200 mesh purity) to lithium fluoride is 1:0.8-3. Preferably, 3g of lithium fluoride is combined with 2.5g-3.5g of MAX phase, heated at 30-50℃. More preferably, 3g of MAX phase is added at 45℃. In this study, it was found that the ratio of MAX phase to lithium fluoride has a certain influence on the completeness of aluminum layer etching and the formation of a complete accordion morphology. Only when the above-specified ratio is achieved can the tea product meet the requirements of this invention.

[0057] After washing, the supernatant solution was tested for acidity, alkalinity, and neutrality. It was found that neutrality was the best, i.e., the optimal pH value was 7, and the ultrasonic time was 40-60 min, with 60 min being the more preferred ultrasonic time.

[0058] This invention also attempted to use MOF, COF, etc. as substrates, but the detection effect of these substrates as electrochemical immunosensors in this experiment could not meet expectations.

[0059] S2. Prepare a mixed solution of tetrachloroauric acid and hexadecyltrimethylammonium bromide, then add a cold sodium borohydride solution, mix rapidly (30-40 seconds), and let stand at room temperature for 2-3 hours to obtain the seed solution. Prepare a growth solution of a mixed solution of tetrachloroauric acid, hexadecyltrimethylammonium bromide, silver nitrate, hydrochloric acid, and ascorbic acid, then add the previously prepared seed solution, mix thoroughly, and let stand at room temperature for 7-9 hours.

[0060] The concentration of the tetrachloroauric acid solution was 0.01-0.04 M.

[0061] The sodium borohydride solution concentration is 0.01-0.03M;

[0062] The volume ratio of tetrachloroauric acid solution to sodium borohydride solution is 1:1-5; if the ratio is incorrect, the synthesis of AuNRs morphology will fail, resulting in poor electrochemical performance.

[0063] The typical growth solution is a mixture of tetrachloroauric acid (0.01-0.03M, 1.5-3ml), hexadecyltrimethylammonium bromide (0.05-0.1M, 30-50ml), silver nitrate (0.01-0.03M, 200-400ul), hydrochloric acid (1-2M, 500-800ul), and ascorbic acid (0.1-0.3M, 300-400ul). The seed solution volume is 150-200ul. Adjusting the components and proportions does not yield the gold rod substance.

[0064] This study found that other precious metals such as Ag and Pt can also be used with this product; however, the study showed that Au had the best effect.

[0065] (3) Prepare a mixed solution of hydrochloric acid and aniline, a mixed solution of ammonium persulfate and hydrochloric acid, centrifuge Au NRs, then mix MXene, Au NRs and water to form a mixed solution and stir evenly, add the mixed solution of hydrochloric acid and aniline and continue stirring for 2-5 hours, finally add the mixed solution of ammonium persulfate and hydrochloric acid, stir for 2-5 hours, centrifuge and wash to obtain MXene@PANI@Au.

[0066] The volume ratio of hydrochloric acid solution to aniline solution is 200-600:1, preferably 1-2M hydrochloric acid solution, 15-20ml, and 40-60ul aniline solution.

[0067] The mass ratio of ammonium persulfate to hydrochloric acid is 1-2:1; preferably, 0.15-0.25g of ammonium persulfate is mixed with 4-6ml of 1-2M hydrochloric acid; the content of the initiator and the stirring time are screened and controlled, and too much or too little initiator dosage and too short or too long stirring time will lead to a decrease in the performance of the final composite product.

[0068] For MXene content of 10-40 mg, use Au NR centrifugation in a volume of 30-40 ml.

[0069] The volume of aniline solution used is 160-170 μL, hydrochloric acid solution (4.5-5 ml, 1-2 M), and the total stirring time is preferably 4-5 hours.

[0070] In this study, chitosan, sodium alginate, and polydopamine were used to replace aniline, but their detection performance as electrochemical immunosensors in this experiment did not meet expectations.

[0071] Example 2. Preparation of bioimmunoassay (electrochemical immunosensing) based on MXene@PANI@Au

[0072] The prepared MXene@PANI@Au liquid gun was dropped onto the screen-printed electrode. After drying, the antibody was activated using EDC and NHS. Then, a certain amount of antibody was dropped onto the electrode using the liquid gun and incubated at a certain temperature.

[0073] The mass ratio of EDC to NHS is 1:1-2, the activation time is 15-20 min, the antibody volume is 5-7 μL added to each electrode, and the antibody incubation time is 15-30 min.

[0074] Best Experimental Example 1: Preparation of MXene@PANI@Au

[0075] First, in a polytetrafluoroethylene reactor, 2 g of LiF was added to 30 mL of 12 mol / L hydrochloric acid and stirred for 30 minutes under ambient conditions. Then, 2 g of Ti3AlC2 MAX phase was added, and the mixture was further stirred for 45 minutes in an oil bath at 45°C. After cooling to room temperature, the product was collected by centrifugation and washed repeatedly with deionized water until the pH of the supernatant was equal to 7. The sample was then sonicated with ethanol for 1 hour to obtain the upper black solution.

[0076] Gold nanorods (NRs) were synthesized using an improved seed-mediated method. Typically, the seed solution is prepared by reducing chloroauric acid (0.01 M, 250 μL) in an aqueous solution of hexadecyltrimethylammonium bromide (0.1 M, 9.75 mL) with ice-cold sodium borohydride (0.01 M, 600 μL). The prepared seed solution (250 μL) was then injected into a growth solution prepared by sequentially adding chloroauric acid (0.01 M, 2 mL), silver nitrate (0.01 M, 400 μL), hydrochloric acid (1 M, 800 μL), and ascorbic acid (0.1 M, 320 μL) to an aqueous solution of hexadecyltrimethylammonium bromide (0.1 M, 40 mL). The samples were collected by centrifugation and washed three times with deionized water for subsequent use.

[0077] 10 mg of MXene was added to 50 mL of deionized water and dispersed uniformly using ultrasound. Separately, 2 μL of aniline solution and 6 mg of ammonium persulfate were dissolved in 10 mL of 1 mol / L hydrochloric acid and then slowly added to the MXene dispersion. A certain amount of gold nanorod solution was then added, and the mixture was stirred at room temperature for 4 hours. Finally, the mixture was washed three times with deionized water to obtain MXene@PANI@Au NRs.

[0078] from Figure 1 It can be seen that Au NRs were successfully loaded on PANI and MXene. From Figure 2 The lattice spacing of Au NRs is 0.235 nm, and that of MXene is 0.35 nm, demonstrating the successful synthesis of Au NRs and MXene. From... Figure 3 and Figure 4 The results show that the characteristic peaks of MXene, PANI, and Au NRs all appear in the MXene@PANI@Au NRs composite material, proving that the three have been successfully composited.

[0079] Best Experimental Example 2: Preparation of MXene@PANI@Au / Ab

[0080] The prepared MXene@PANI@Au liquid gun was used to drop the solution onto the screen-printed electrodes of both electrodes. After drying, the carboxyl groups on the PCT antibody and L-6 antibody were activated for 15 min using EDC and NHS (mass ratio of 1:2). PCT and IL-6 were then dropped onto their respective electrodes. After the amino functional groups on the PANI react with the carboxyl groups on the antibody, the antibody was fixed on the material surface. Then, a certain amount of corresponding antibody (PCT / IL-6) 5 μL was dropped onto the electrode using a liquid gun and incubated at 37 °C for 30 min.

[0081] Example 3: Sensor Testing

[0082] 1. Fabrication of PCT / IL-6 sensor electrode assembly

[0083] 5 μL of MXene@PANI@Au NRs solution was added dropwise to the working electrode of the screen-printed electrode using a liquid pipette, and the electrode was placed on a heating stage and heated until dry. Then, 5 μL of PCT / IL-6 antibody activated with EDC and NHS (1:2) was added dropwise, and the electrode was incubated at 37°C for 30 min. After that, the electrode was connected to the electrochemical workstation.

[0084] 2. Preparation of electrolyte

[0085] Weigh 165 mg of potassium ferricyanide and 185 mg of potassium ferrocyanide and add them to 100 ml of PBS solution. Sonicate for 10 min to obtain a uniform yellow transparent solution.

[0086] 3. Testing Process

[0087] Add 60 μL of electrolyte solution to the screen-printed electrode, ensuring that the working electrode, reference electrode, and counter electrode are completely covered by the electrolyte solution. Select the DPV test mode of the electrochemical workstation, with a test voltage range of -0.2V to 0.6V.

[0088] from Figure 5 and Figure 6 As can be seen, with the increase of PCT protein concentration, the peak current height of DPV decreases instead, and there is a good linear relationship between concentration and current response. The theoretical detection limit is 0.84 pg / ml.

[0089] from Figure 7 and Figure 8 As can be seen, there is a good linear relationship between concentration and current response as the concentration of IL-6 protein increases, but the peak current height of DPV decreases instead, and the theoretical detection limit is 0.74 pg / ml.

[0090] Example 4:

[0091] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (20 mM) and N-hydroxysuccinimide (10 mM) were added to a procalcitonin antibody (anti-PCT, 0.1 mg / mL) solution and placed on a shaker for 15 minutes to activate the carboxyl groups on the antibody surface. 5 μL of anti-PCT (Ab) solution was added to the surface of MXene@PANI@Au NRs / SPE and reacted at 37 °C for 1 h. The carboxyl groups on the anti-PCT surface reacted with the amino groups on the surface of MXene@PANI@Au NRs / SPE, immobilizing the antibody on the electrode surface. After the reaction, the electrode was washed with PBS, and 6 μL of 1 mg / mL BSA was added to the electrode surface and incubated for 30 minutes to block the surface active sites, reducing non-specific adsorption of non-target proteins on the electrode surface. Finally, unbound BSA was washed away with PBS to obtain the BSA / Ab / MXene@PANI@Au NRs / SPE electrode. For PCT antigen concentration detection, different concentrations of the test solution were added to the surface of the prepared immunosensor, incubated for 1 hour, and then rinsed with PBS. The prepared electrode was stored at 4°C and removed for testing. The construction of the IL-6 protein electrochemical immunosensor was the same as described above. Further investigation was conducted on the long-term stability of the sensor under 4°C storage conditions. Figure 9 The test results for 31 consecutive days showed that the DPV current response value remained above 81.9% of its initial value. In the anti-interference test... Figure 10The sensor exhibited a significant specific response to PCT at 20 ng / mL for seven potential interfering substances, including lactate, cardiac troponin (cTni), glutathione, ascorbic acid, glucose, dopamine, and myoglobin, with response rates to all interfering substances below 6%, confirming its excellent selectivity. Furthermore, preliminary tests were conducted on clinical samples, including serum from a confirmed sepsis patient and several healthy donors. The sensor successfully distinguished patients from healthy individuals based on procalcitonin (PCT) and interleukin-6 (IL-6) levels, with results consistent with simulated data. Figure 11 ).

[0092] The function and effect of this embodiment:

[0093] This embodiment uses a large specific surface area two-dimensional MXene as a substrate, PANI as the antibody immobilization host, and Au as the signal amplification to prepare an MXene@PANI@Au composite material. This nanocomposite material is obtained by self-assembling a three-dimensional network of PANI and Au on the MXene surface using a chemical reduction method. The obtained MXene@PANI@Au nanocomposite material is mixed with deionized water to form a suspension. The solution is then dropped onto the surface of a screen-printed electrode using a liquid gun and dried. IL-6 or PCT antibodies are activated via EDC / NHS and then dropped onto the electrode. After drying, a sensor element for detecting IL-6 or PCT proteins can be prepared. The electrochemical performance of the material is tested using an electrochemical workstation testing system. This electrochemical biosensor exhibits strong anti-interference ability, high sensitivity, good selectivity to interfering substances, and good stability in the detection of IL-6 and PCT proteins, and can be used for the detection of other disease proteins in the human body.

Claims

1. A composite material MXene@PANI@Au, characterized in that: MXene@PANI@Au composite material composed of MXene, PANI and Au.

2. The method for preparing the composite material MXene@PANI@Au as described in claim 1, characterized in that: PANI was synthesized in situ in a mixed solution of MXene and Au NRs via wet chemical method and one-pot method, forming a tertiary composite material of MXene@PANI@Au.

3. The method for preparing the composite material MXene@PANI@Au as described in claim 2, characterized in that: In the process of in-situ synthesis of PANI, aniline is used as the monomer, and an oxidant and an initiator are also required.

4. The method for preparing the composite material MXene@PANI@Au as described in claim 2, characterized in that: The preparation method of the MXene is as follows: SX1. Mix lithium fluoride with hydrochloric acid and stir at room temperature. The mass ratio of lithium fluoride to hydrochloric acid is 1:3-10. SX2. Add MAX phase and heat at 30-50℃ for 40-60 min. The mass ratio of MAX phase to lithium fluoride is 1:0.8-3. SX3. Wash with water and centrifuge until pH reaches 6.5-7.5; SX4. Add ethanol and sonicate to obtain a black precipitate, which is MXene.

5. The method for preparing the composite material MXene@PANI@Au as described in claim 2, characterized in that: The preparation method of the Au NRs is as follows: SA1. Mix tetrachloroauric acid and hexadecyltrimethylammonium bromide, with the tetrachloroauric acid solution concentration being 0.01-0.04M; SA2. Add ice-cold sodium borohydride solution, mix quickly, and let stand at room temperature for 2-3 hours to obtain the seed solution. The concentration of sodium borohydride solution is 0.01-0.03M, and the volume ratio of tetrachloroauric acid solution to sodium borohydride solution is 1:1-5. SA3. Prepare the growth solution, namely, a mixed solution containing tetrachloroauric acid, hexadecyltrimethylammonium bromide, silver nitrate, hydrochloric acid, and ascorbic acid; SA4. Add the seed solution prepared in S2 to S3, mix well, and let stand at room temperature for 7-9 hours.

6. The method for preparing the composite material MXene@PANI@Au as described in claim 2, characterized in that: S1. Prepare a mixed solution of hydrochloric acid and aniline, and a mixed solution of ammonium persulfate and hydrochloric acid; S2. Centrifuge the Au NRs; S3. Mix MXene, Au NRs and water to form a homogeneous solution; S4. Add the mixed solution of hydrochloric acid and aniline from S1 and continue stirring for 2-5 hours; S5. Add the mixed solution of ammonium persulfate and hydrochloric acid from S1 and continue stirring for 2-5 hours.

7. Application of the composite material MXene@PANI@Au in the fabrication of biological immune sensors.

8. The method for preparing the biological immune sensor as described in claim 7, characterized in that: After drying MXene@PANI@Au on a screen-printed electrode, add the EDC and NHS activated antibody onto the electrode and incubate for 15-30 minutes. The mass ratio of EDC to NHS is 1:1-2; the activation time is 15-20 min; and 5-7 μL of PCT antibody or IL-6 is added to each electrode.

9. Application of the composite material MXene@PANI@Au in the preparation of products for detecting / identifying PCT and / or IL-6 protein.

10. Application of the composite material MXene@PANI@Au in the preparation of products for sepsis diagnosis or early screening.